Forecasting the potential output and growth of the manufacturing industry: a case study of Indonesia's manufacturing sector - Permana, Tirta Wisnu; Yudoko, Gatot; Prasetio, Eko Agus (Jurnal Ekonomi & Studi Pembangunan, 2023)
Indonesia is currently experiencing deindustrialization, characterized by a manufacturing industrial sector growth rate lower than the overall economic growth rate. Therefore, it is necessary to encourage the development of the industrial sector to achieve sustainable development. The scenario for industrial development policy is determined based on an evaluation of the country's economic position in relation to current business cycle conditions. The evaluation is carried out through output gap analysis, which refers to the gap between actual and potential output. The research aim is to analyze output potential estimates and gaps in the Indonesian non-oil and gas processing industry sector. The methodology used in this research includes the HP Filter (Hodrick-Prescott), BP Filter (Band-Pass), and the Production Function Approach. The findings show that Indonesia's non-oil and gas processing industry experienced a slight decline below its potential between 2020 and 2021. Therefore, policymakers must consider this; in the short term, inflationary pressures are caused by a positive output gap, so the government needs to prioritize efforts to control inflation. Meanwhile, medium-term structural reforms must continue to increase potential output, including increasing labor force participation, sustainable investment for capital factors, and improving the quality of human resources and technological expertise for productivity factors. In particular, it is necessary to pay attention to the adoption of new emerging technologies.